2021
DOI: 10.1029/2020sw002620
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Thermospheric Density Estimation via Radar and GPS Tracking Data Assimilation

Abstract: Thermospheric density is estimated using a reduced-order density model and radar 7 range and range-rate tracking data and GPS measurements. 8 • The estimated densities are validated against accurate SWARM density data. 9 • The obtained densities are significantly more accurate than NRLMSISE-00 and 10 JB2008 modelled densities and TLE-estimated densities.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The high‐frequency density estimates, corrected for the drag‐coefficient biases with our proposed framework, can be a useful data source for such a method. Gondalech and Linares (2021) estimated the ballistic coefficient simultaneously with the local densities in their data‐assimilation technique. But the ballistic coefficient biases had to be calculated through several‐day estimation runs and corrected for the density biases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high‐frequency density estimates, corrected for the drag‐coefficient biases with our proposed framework, can be a useful data source for such a method. Gondalech and Linares (2021) estimated the ballistic coefficient simultaneously with the local densities in their data‐assimilation technique. But the ballistic coefficient biases had to be calculated through several‐day estimation runs and corrected for the density biases.…”
Section: Discussionmentioning
confidence: 99%
“…This can be remedied by using reduced‐order models to represent them with a smaller subset of parameters (Mehta & Linares, 2017, 2018). This technique has been used to demonstrate the estimation of global atmospheric density by assimilating measurements from accelerometers (Mehta et al., 2018), two‐line element data (Gondalech & Linares, 2020), and radar and GPS measurements (Gondalech & Linares, 2021). All such data‐assimilation methods significantly improve global atmospheric density estimates over existing semi‐empirical models.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) used PCA on TIE‐GCM data and developed a dynamic ROM using DMD with control (or DMDc). This approach has been applied by Gondelach and Linares (2020, 2021) on the NRLMSISE‐00, JB2008, and TIE‐GCM models with the goal of data assimilation. DMDc is based on the assumption of the linear relationship between successive time steps and the processes that drive the system, rightboldxk+1=Axk+Buk $\begin{array}{r}\hfill {\mathbf{x}}_{k+1}={\mathbf{A}\mathbf{x}}_{k}+{\mathbf{B}\mathbf{u}}_{k}\end{array}$ where x denotes the state, A is the dynamic matrix, and B is the input matrix relating the system inputs/drivers and successive state of the system.…”
Section: Methodsmentioning
confidence: 99%
“…This work was extended using accelerometer-derived density estimates from the Challenging Minisatellite Payload (CHAMP) and Gravity Field and Steady-State Ocean Circulation Explorer (GOCE) [96] satellites and TLE data [97] for model calibration. Gondelach and Linares [98] showed that a ROM model with TLE-estimated densities provides more precise Orbit Determination than the NRLMSISE-00 and JB2008 models, especially in the along-track coordinate. This ROM approach was improved upon using an anto-encoder for dimensionality reduction [99].…”
Section: Thermospheric Density Mass Modelsmentioning
confidence: 99%